Functional Connectivity Differences in the Insular Sub-regions in Migraine without Aura: A Resting-State Functional Magnetic Resonance Imaging Study - Yu, Zhi-bo; Lv, Yan-bing; Song, Ling-heng; Liu, Dai-hong; Huang, Xue-ling; Hu, Xin-yue; Zuo, Zhi-wei; Wang, Yao; Yang, Qian; Peng, Jing; Zhou, Zhen-hua; Li, Hai-tao (Frontiers in Behavioral Neuroscience, 2017)
Objective: The objective of this study was to investigate resting-state functional connectivity (FC) differences in insular sub-regions during the interictal phase in patients with migraine without aura (MWoA). Methods: Forty-nine MWoA patients (MWoA group) and 48 healthy individuals (healthy control group) were recruited for this study. All of the subjects underwent neurological examination and magnetic resonance imaging (MRI). The MRI data were processed using Brat 1.0 software to obtain a whole-brain FC diagram and using Rest 1.8 software to obtain the FC z-score of the sub-regions of both insulas (six sub-regions on each side). Therefore, there were a total of 12 regions of interest (ROIs) that were used as seed points for the statistical analysis. Results: There was abnormal FC between the insular sub-regions and multiple brain regions in the MWoA patients compared with the healthy control group, and a clear laterality was also observed. In addition, the FC z-score of certain sub-regions was negatively correlated with the disease duration. Conclusion: Different insular sub-regions are functionally associated with different regions of the brain and therefore have different functions. In MWoA, the FC between the insular sub-regions and other brain regions was mostly reduced, while a small amount was increased; additionally, the FC may be ipsilateral with a right-side advantage. Variations in the FC of insular sub-regions can be observed as an important indicator of MWoA.